1960
DOI: 10.1139/v60-240
|View full text |Cite
|
Sign up to set email alerts
|

AN IMPROVED TECHNIQUE FOR THE OBSERVATION OF INFRARED CHEMILUMINESCENCE: RESOLVED INFRARED EMISSION OF OH ARISING FROM THE SYSTEM H + O2

Abstract: A ~nultiple reflection apparatus for the observation of infrared chemiluminescence is described. By means of this apparatus infrared emission from the system H + 0 2 has been identified as being due to vibrationally excited OH radicals in levels v = 1, 2, and 3 of the ground electro~iic state. The resolved infrared spectrum of the OH fundamental has been observed for, the first time without interference from other emission. The most likely source of excited OH is the reaction H + 1302 --r O H t + OH. The vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The comparable reaction with H atoms, reaction 3, would also be potentially important in an O2 containing system and is known to produce OH(u < 4). 32 To produce the observed absolute concentration of OH(u = 9) from these lower vibrational levels requires a rate constant for ( 5 ) exceeding gas kinetic. Upper limit calculations to the pumping rate via vibration-vibration exchange can be made as illustrated in Table I11 by applying a gas kinetic rate constant.…”
Section: Comparison Of Experimental Observation and Model Predictionsmentioning
confidence: 99%
“…The comparable reaction with H atoms, reaction 3, would also be potentially important in an O2 containing system and is known to produce OH(u < 4). 32 To produce the observed absolute concentration of OH(u = 9) from these lower vibrational levels requires a rate constant for ( 5 ) exceeding gas kinetic. Upper limit calculations to the pumping rate via vibration-vibration exchange can be made as illustrated in Table I11 by applying a gas kinetic rate constant.…”
Section: Comparison Of Experimental Observation and Model Predictionsmentioning
confidence: 99%
“…The mirrors were supported from the outer wall of the vessel. 35 These mirrors, designed for use in the 2-5 p, range, were front-surface coated with gold.…”
Section: Experimentfalmentioning
confidence: 99%
“…The apparatus has been described previously. 16 In the present work, in addition to coating the reaction vessel with phosphoric acid, a phosphoric-coated Pyrex lining was placed inside the vessel in the hope of decreasing the loss of H atoms at the wall. The four discharge tubes were drawn down to 3 mm at their tips.…”
Section: Resultsmentioning
confidence: 99%
“…An apparatus with 120 times the reaction volume of that used in our earlier work on H+Clz, and with internal mirrors to collect the radiation, has already been described in connection with an investigation of the system H + 02. 16 A preliminary investigation of the reactions H + Cl2 and H + NOCl in this apparatus 17 showed that at -10-2 mm Hg total pressure ( N 10-1 times the total pressure used in the earlier work) the stationary distribution of HClt in the reaction vessel was markedly non-Boltzmann. Emission previously observed from the highest vibrational levels was no longer observed at the low pressure.…”
mentioning
confidence: 80%